2018
DOI: 10.4103/ortho.ijortho_359_16
|View full text |Cite
|
Sign up to set email alerts
|

Does the Surgeon-reported Outcome Correlate with Patient-reported Outcome after Total Knee Arthroplasty? A Cohort Study

Abstract: Background:Total knee arthroplasty (TKA) has been proved to be a successful and cost-effective treatment for improving pain and function in patients with knee arthritis. Total knee arthroplasty (TKA) is one of the most common orthopaedic surgeries performed worldwide and advancement in surgical techniques and prosthetic designs have improved the patient outcomes. However, concerns and priorities of patients and surgeons relating to joint replacement may differ.Materials and Methods:306 TKAs in 223 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…
Total knee arthroplasty (TKA) is one of the most common orthopedic surgeries performed worldwide [1]. TKA has proved to be a successful and cost-effective treatment for improving pain and function in patients with advanced knee arthritis.
…”
mentioning
confidence: 99%
“…
Total knee arthroplasty (TKA) is one of the most common orthopedic surgeries performed worldwide [1]. TKA has proved to be a successful and cost-effective treatment for improving pain and function in patients with advanced knee arthritis.
…”
mentioning
confidence: 99%
“…Interest in PROM has increased exponentially over the past 15 years and includes quantitative and/or qualitative components. 4 , 5 Previous studies have shown the importance of qualitative analysis in providing a framework for PROM production. 6 8 However, the limited number and heterogeneity of FT procedures performed to date make it particularly challenging to recruit the research sample that would be needed to develop PROMs specific to FT recipients.…”
Section: Introductionmentioning
confidence: 99%